Less adaption of newly approved variety Basmati 515 among aromatic basmati rice varieties in Kallar Tract of Punjab, Pakistan - Muhammad Tahir Latif (Azarian Journal of Agriculture, 2017)
A field survey was conducted after harvesting of rice crop 2016 to identify the reasons for less adaption of aromatic rice variety Basmati 515. The rice growers adopting rice-wheat cropping pattern in kallar tract were included in population of research study. Thirty male farmers from each selected district making a total of 180 respondent farmers were interviewed by convenience sampling method. The survey findings showed that the aromatic rice variety Basmati 515 was cultivated on only 2.7% rice area while maximum area (47.3%) was under Super basmati variety. The comparison of Basmati 515 was made with Super basmati and PS 2 due to comparatively more cultivated area and declared yield potential of these varieties. Overall the farmers were applying under dosed phosphorus fertilizer (DAP) as 0.25, 0.20 and 0.22 bag ha-1 respectively for basmati 515, super basmati and PS-2 varieties. The descriptive analysis showed that the less adaptability of basmati 515 was due to less yield and more attacks of borer (11%), BLB (10%) and leaf roller (3.25%) in comparison to other aromatic and fine rice varieties. Similarly maximum lodging (16%) was recorded on basmati 515. Maximum yield was estimated for PS 2 variety (4.7 t ha-1) followed by super basmati (4.0 t ha-1) and basmati 515 (3.78 t ha-1). The market price of super basmati was still higher due to its natural aroma, long & thin grain and export demand. The research institutes should focus for development of new aromatic high yielding and more qualitative rice varieties to increase the rice production and export.